Ethnic Diversity and Preferences for Redistribution - Regression Data - Lundqvist, Heléne; Edmark, Karin; Dahlberg, Matz (Uppsala University, 2012)
Ethnic Diversity and Preferences for Redistribution attempts to explain if individual's preferences for redistribution change if the ethnic diversity increases in a municipality. In this case, selected parts of the Swedish Election Studies has been matched with municipal data for the time period between 1985 and 1994, when Sweden had an active placement program of refugees. This meant that the refugees themselves were not allowed to decide where to settle, but instead they were places in municipalities which had contracts with the Swedish Integration Board (Invandrarverket). Originally the idea of the program was to direct the refugees to municipalities with good labor market conditions, but since the number of refugees arriving to Sweden were larger than expected, so in practice more or less all municipalities were a part of the program. With the placement program refugees spread more across the country, than before the program. Ethnic Diversity and Preferences for Redistribution focus primarily on refugees from nations which not were members in the OECD 1994 and Turkey.

The data comes from the Swedish Election Studies survey waves for the elections in 1982, 1985, 1988, 1991 and 1994. Primarily it consists of various background variables and variables about individual's preferences for private health care, nuclear power and social benefits. The municipal data primarily consist of various socio-economic and political variables, such as population, tax base, welfare spending and share of refugees. Some of these variables are the average of the term (1986-1988, 1989-1991, and 1992-1994).

Purpose:

Investigate the causal link between the ethnic diversity in a society and its inhabitants´ preferences for redistribution.

Ethnic Diversity and Preferences for Redistribution försöker att belysa om individers preferenser kring omfördelning förändras i och med att den etniska mångfalden i en kommun ökar. I detta fall har utvalda delar från Svensk valundersökning matchats ihop med kommundata under perioden 1985 till 1994, då Sverige hade ett aktivt utplaceringsprogram av flyktingar. Detta innebar att flyktingarna inte själva fick bestämma var de skulle bosätta sig, utan att de istället placerades i kommuner enligt kommunvisa avtal med Invandrarverket. Från början var tanken att styra flyktingarna mot kommuner som hade gynnsamma arbetsmarknadsförhållanden, men eftersom flyktinginvandringen blev större än förväntat kom i praktiken i stort sett alla kommuner att omfattas. I och med utplaceringsprogrammet blev flyktingmottagandet mer spritt över landet. I Ethnic Diversity and Preferences for Redistribution fokuserar främst på de flyktningar/invandrare som kommer från nationer som inte var medlemmar i OECD 1994 samt Turkiet.

Datamängden som är hämtad från den Svenska valundersökningen är från undersökningsvågorna för 1982, 1985, 1988, 1991 och 1994 års val. Främst handlar det om variabler kring olika bakgrundsfaktorer och kring individers preferenser för privat hälsovård, kärnkraft samt för sociala bidrag. Den kommunala datan består främst av olika socioekonomiska och politiska variabler såsom population, skattebas, välfärdsutgifter och andelen invandrare. Vissa av dessa variabler är genomsnittet för mandatperioden (1986-1988, 1989-1991 och 1992-1994)

Syfte:

Att undersöka orsakssambandet mellan den etniska mångfalden i ett samhälle och dess invånares preferenser för omfördelning.
Ethnic Diversity and Preferences for Redistribution - Regressiondata
Keywords: social welfare; social välfärd; income distribution; inkomstfördelning; social welfare expenditure; utgift för social välfärd; immigrants; invandrare; parliamentary elections; riksdagsval; voting behaviour; väljarbeteende; immigration policy; invandringspolitik; internal politics; inrikespolitik; electoral issues; valfrågor; welfare policy; social- och välfärdspolitik; Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Social welfare policy; Välfärdspolitik; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Economics; Nationalekonomi